2013
DOI: 10.3109/13880209.2012.749920
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of Juglans regia extract against CCl4-induced oxidative damage in rats

Abstract: Context: Different parts of the walnut [Juglans regia L. (Juglandaceae)] have been used in folk medicine for protection against liver injury, although its actual efficacy remains uncertain. Objective: The present study investigated the protective effect of walnut leaf extract against carbon tetrachloride (CCl 4 )-induced liver damage in rats. Materials and methods: The rats were randomly divided into seven groups: control, CCl 4 (i.p., 0.5 mL/kg b.w., 50% CCl 4 in olive oil), walnut extract (at dose level of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 44 publications
5
45
0
2
Order By: Relevance
“…For instance, Ren and Meng reported the use of GHJ drug cocktail therapy in the treatment of liver cancer [20]. Eidi investigated the protective effect of walnut extracts against carbon tetrachloride (CCl4)-induced liver damage in rats [21]. Their results indicated that GHJ had an important role in assisting chemotherapeutic drugs to inhibit liver tumor metastasis and acting as a good hepatoprotective and antioxidant agent in attenuating hepatocellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ren and Meng reported the use of GHJ drug cocktail therapy in the treatment of liver cancer [20]. Eidi investigated the protective effect of walnut extracts against carbon tetrachloride (CCl4)-induced liver damage in rats [21]. Their results indicated that GHJ had an important role in assisting chemotherapeutic drugs to inhibit liver tumor metastasis and acting as a good hepatoprotective and antioxidant agent in attenuating hepatocellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Under laboratory conditions, a number of chemical compounds such as CCl 4 , thioacetamide and N 0 -nitrosodiethylamine (NDEA) induce hepatic fibrosis (Bruck et al, 2001;Eidi et al, 2013;George et al, 2001;Krajka-Kuzniak et al, 2012). However, N 0 -nitrosodimethylamine (NDMA) has the advantage of inducing fibrosis within shortest duration of 21 days, with lesser animal mortality and better reproducibility (George & Chandrakasan, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies regarding pharmaceutical effects of walnut leaf (Kaumar et al, 2003); therefore it can be a good candidate for using it as antimicrobial agent against bacteria responsible for human gastro-intestinal and respiratory tract infections (Pereira et al, 2007) and antiproliferative effects (Salimi et al, 2012). Eidi et al (2013) demonstrate that walnut extract acts as a good hepatoprotective and antioxidant agent in attenuating hepatocellular damage. Ellagic acid, a phenolic acid, is a major component of walnuts, and it has been suggested that it exerts antiatherogenic, anticarcinogenic and antioxidative properties (Anderson et al, 2001;Mertens-Talcott et al, 2003;Narayanan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%